How Pregnancy Influence Promotion for High-skilled Women in Urban China: A Qualitative Research - Fang, Zhi (2020)
The trends of promoting gender equality and increasing women status has become popular all over the world and China is no exception. This research has focused on the analysis that in what ways pregnancy has influenced high-skilled women’s promotion in urban China. In order to find out more detailed results, qualitative research method would be selected. Fourteen participants working in Chinese public sectors and private companies were selected to take part in the semi-structured interview. Based on the results, the different experiences suffered by the participants would be further discussed to disclose the overall development gap and the inadequate supervision in urban China. It is found that the overall influence of pregnancy on working women’s promotion is negative and relative influences would also be further discussed. 4